Business-to-business marketing - Brennan, Ross 1957-; Canning, Louise; McDowell, Raymond (London Los Angeles SAGE, 2011)
This volume examines views that argue business to business marketing is simply a variant of consumer marketing or is only concerned with inter-organizational relationship management
Previous ed.: 2007
Includes bibliographical references and index
2
Keywords: Industrial marketing -- Case studies; Industrial marketing